Teacher–Centred and Student–Centred Learning Environments - Zulfizar Qo'chqorova (Journal of Innovation in Education and Social Research, 2023)
This article discusses two different approaches: student-centered and teacher-centered. This is approached through first examining the general differences between the two learning approaches in terms of the activities involved, the learning environment, and positions held by either the teacher or student in either approach. The advantages of both approaches, the role of these methods in the field of education are comprehensively considered and extensively illustrated through examples.